Macroeconomics of imperfect competition and nonclearing markets a dynamic general equilibrium approach - Benassy Jean-Pascal (Cambridge MIT Press, 2002)
In this book, Jean-Pascal Benassy attempts to integrate into a single unified framework dynamic macroeconomic models reflecting such diverse lines of thought as general equilibrium theory, imperfect competition, Keynesian theory, and rational expectation
Keywords: Equilibrium(Economics); Imperfect competition; Keynesian economics; Macroeconomics; Mathematical models; Rational expectations(Economic theory)